The collected works of Thomas Kyd, Volume one - Kyd, Thomas 1558-1594 (Studies in Renaissance literature (Woodbridge, Suffolk, England), 2024)
The first complete, integrated corpus of Kyd and first critical edition of his collected works in over one hundred years, with major new discoveries of authorship and attribution. Thomas Kyd (1558-94) is best known as author of The Spanish Tragedy, the first revenge play, hugely influential on Shakespeare and other dramatists. He also wrote another love tragedy, Soliman and Perseda, and Cornelia, a classical tragedy translated from the French. This is a small canon for a dramatist described as "industrious". Kyd worked between 1585 and 1594, when the instability in the London theatre caused by the plague led to companies breaking up and plays being published anonymously. For over a century scholars have been searching for Kyd plays, the most frequently attributed being Arden of Faversham. Uniting accepted methods with modern electronic data processing, Brian Vickers has endorsed Kyd's authorship of Arden and added two other plays: King Leir, Shakespeare's main source, and Fair Em, a comedy - justifying Jonson's reference to "sporting Kyd". His research has also identified Kyd as co-author with Nashe of 'harey the vi', which became 1 Henry VI after Shakespeare adapted it to his "Wars of the Roses" sequence. The evidence suggests that Kyd and Shakespeare co-authored Edward III. The Collected Works of Thomas Kyd brings together for the first time his dramas, poetry, translations, and letters in accurate modernized editions, each text edited by one of a team of internationally renowned scholars, accompanied by commentaries, collation notes, and introductions. Kyd emerges as a pioneering playwright of much greater generic range than has been hitherto recognized. His newly defined canon will stimulate a fresh evaluation of English drama in this crucial period